Irrigation First Five Year Plan an Appraisal - Planning Commission (Planning Commission)
In a predominantly Agricultural Economy where 70.9 percent of the people depend on agricultural pursuits, the importance of developing irrigation need hardly be emphasized. Successful farming depends on the presence of enough moisture in the soil to enable plants to grow and mature. Even in areas where the rainfall average is good, large scale failures of Kharif crop occur in seasons of draught, while in Rabi most crops have to be given artificial watering to obtain satisfactory yield. Irrigation is, therefore, as old as agriculture.
Irrigation